Optochemical nanosensors - Cusano, Andrea (Boca Raton, Fla. : CRC Press, 2013)
'This book provides an overview of the state-of-the-art in optical and chemical nanosensors for industrial, environmental, diagnostic, security, and medical applications. It summarizes the various types and developments in optical and chemical sensor technology and then explains how the integration of optical/chemical sensors and nanomaterials creates new opportunities. The text also reviews optochemical sensors, starting from the basics in optoelectronics and concluding with the principles of operation at the basis of optochemical devices. The authors offer insight into future trends in this growing field and present a range of applications in the fields of medicine, security, and bioterrorism'--
part. 1. Basics -- part. 2. Research advances -- part. 3. Applications.
'A Taylor & Francis book.'
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Chemical detectors; Optical detectors; Nanoelectromechanical systems; Biosensors